Perceptions of provider awareness of traditional and cultural treatments among Indigenous people who use unregulated drugs in Vancouver, Canada - Alexa Norton; Fahmida Homayra; Courtney Defriend; Brittany Barker; Louise Meilleur; Kanna Hayashi; Bohdan Nosyk (BMC, 2024)
Abstract Introduction Indigenous people who use unregulated drugs (IPWUD) face significant barriers to care, including sparse availability of culturally safe health services. Integrating Indigenous traditional and cultural treatments (TCT) into health service delivery is one way to enhance culturally safe care. In a Canadian setting that implemented cultural safety reforms, we sought to examine the prevalence and correlates of client perceptions of primary care provider awareness of TCT among IPWUD. Methods Data were derived from two prospective cohort studies of PWUD in Vancouver, Canada between December 2017 and March 2020. A generalized linear mixed model with logit-link function was used to identify longitudinal factors associated with perceived provider awareness of TCT. Results Among a sample of 507 IPWUD who provided 1200 survey responses, a majority (n = 285, 56%) reported their primary care provider was aware of TCT. In multiple regression analyses, involvement in treatment decisions always (Adjusted Odds Ratio [AOR] = 3.6; 95% confidence interval [CI]: 1.6-7.8), involvement in treatment decisions most or some of the time (AOR = 3.3; 95% CI: 1.4-7.7), comfort with provider or clinic (AOR = 2.7; 95% CI: 1.5-5.0), and receiving care from a social support worker (AOR = 1.5; 95% CI: 1.0-2.1) were positively associated with provider awareness of TCT. Conclusion We found high levels of perceived provider awareness of TCT and other domains of culturally safe care within a cohort of urban IPWUD. However, targeted initiatives that advance culturally safe care are required to improve healthcare and health outcomes for IPWUD, who continue to bear a disproportionate burden of substance use harms.